Effects of metal ion implantation (Fe, Ti, Zn and Zr) on mechanical properties, corrosion resistance and biocompatibility of WE43 Mg alloy - Lianhui Li; Zhiqiang Zhang; Dechuang Zhang; Fugang Qi; Yilong Dai; Wenwen Wei; Xiaoping Ouyang (Journal of Magnesium and Alloys)
To improve the corrosion resistance of biodegradable Mg alloys, WE43 alloys were implanted with Fe, Ti, Zn and Zr ions at the same implantation dose. The surface morphology, valence state of elements, nano-hardness (NH), elastic modulus (EM), degradation rate and in vitro cell experiments of the modified WE43 alloys were systematically studied. A modified layer composed of Mg, MgO, the implanted elements and their oxides was formed on the modified alloys. Since high-speed metal ions caused severe surface lattice damage, the surface hardness of the substrate considerable increased. Electrochemical tests demonstrated a substantial enhancement in the corrosion resistance of the modified alloys via the implantation of Ti and Zr ions, resulting in a reduction of the corrosion current density to 88.1 ± 9.9 and 15.6 ± 11.4 µA cm−2, respectively, compared with the implantation of Fe and Zn ions. Biocompatibility tests showed that the implantation of Fe, Ti, Zn and Zr ions enhanced the anticoagulant and hemolytic resistance of the WE43 alloy. All surface-modified samples showed negligible cytotoxicity (0–1) at 12.5% extract concentration. Moreover, the alloys implanted with Fe, Ti and Zn ions significantly promoted proliferation of human umbilical vein endothelial cells (HUVEC) compared with the unmodified alloy. The results demonstrate that Ti ion implantation is the best choice for WE43 alloy modification to achieve outstanding corrosion resistance and biocompatibility.